Extracranial-intracranial bypass grafts - Khodadad, G. (1972)
An extracranial-intracranial bypass graft was established in 16 dogs. The graft was routed deep in the lateral pharyngeal space as opposed to the subcutaneous course in front of the ear, which may be hazardous. Of 10 common carotid-middle cerebral arterial bypass grafts three were still patent four and a half, six, and 11 months postoperatively. The remaining seven arterial and six venous bypass grafts were occluded either at the first angiogram 1 to 14 days after the operation or at the second angiogram 4 to 9 weeks later. The low patency rate in this experiment is attributed to the very small external diameter (average 0·8 mm) of the recipient artery, to donor-recipient discrepancy, to spasm and possibly oedema of the graft. To our knowledge this is the first report on patent extracranial-intracranial bypass grafts in a laboratory animal.